EXPANSION TREND: INDONESIA'S PALM OIL SECTOR GOVERNMENT PLANTATION HEADING FOR EXTINCTION: EXPANSION TREND: INDONESIA'S PALM OIL SECTOR GOVERNMENT PLANTATION HEADING FOR EXTINCTION - Ovi Vensus Hamubaon Samosir (Kajian Asia Pasifik, 2023)
Palm Oil plantations in Indonesia are experiencing a trend of land expansion. The land expansion makes Indonesia, the country with the largest palm oil plantation land in the world, and at the same time the world's largest producer of palm oil. Land expansion is carried out by Government Plantation, Smallholders Plantation, and Private Plantation. However, when observed in more detail, land expansion from Government Plantation has not shown a significant increase and has recently decreased. Seeing the decline in the land area of Government Plantation amid the trend of land expansion of palm oil plantations in Indonesia, this paper argues that liberalization encourages the government to reduce its economic activity in the palm oil plantation sector, and provides opportunities for the market to develop Smallholders Plantation and Private Plantation. Liberalization encouraged the expansion of plantation land nationally, but limited the increase in the land area of Government Plantation. Keyword: Oil palm plantation, Expansion, Government Plantation, Smallholders Plantation, Private Plantation, Liberalization